Estudo sobre as espécies brasileiras de Astraea Röding, 1798 (Mollusca, Gastropoda, Turbinidae) - Monteiro, Júlio Cesar (1997)
The species of genus Astraea Röding, 1798, A. (Astralium) latispina (Philippi, 1844) and A. (Lithopoma) olfersii (Philippi, 1846), were study based on shell, opercula, external morphology of soft parts, mantle cavity, digestive and urogenital systems, similarities and diferences are regarded and discussed, the respective synonymies are given. The comparative conchology of the Brazilian species with A. (Astralium) phoebia Röding, 1798 and A. (Lithopoma) americana (Gmelin, 1791) showed that they are valid species but the references are regarding equivocated occurence for Brazil. The general features of supraspecific taxons and the necessary comparison on study of soft parts of the superfamily species realized based on bibliografic's information with respectives regardfulness and discussions.